2007
DOI: 10.1097/brs.0b013e31815a5a44
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain in 15- to 16-Year-Old Children in Relation to School Furniture and Carrying of the School Bag

Abstract: The present study does not support the hypothesis of different types of school furniture being a causative or preventing factor for LBP. Carrying the school bag in an asymmetric manner may play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 40 publications
3
51
1
13
Order By: Relevance
“…The results show that the prevalence of back pain in the previous three months (54.1%) was within the 20-70% range reported in the literature [4][5][6] . Skoffer 4 , in evaluating the occurrence of pain in 546 students of both genders between 14 and 17 years of age in a town in Denmark, found that 51.3% of the subjects reported having felt pain in the three months prior to the survey; of these subjects, approximately one-quarter (24.2%) reported that this pain resulted in changes in sleeping habits and in seeking specialized medical care.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results show that the prevalence of back pain in the previous three months (54.1%) was within the 20-70% range reported in the literature [4][5][6] . Skoffer 4 , in evaluating the occurrence of pain in 546 students of both genders between 14 and 17 years of age in a town in Denmark, found that 51.3% of the subjects reported having felt pain in the three months prior to the survey; of these subjects, approximately one-quarter (24.2%) reported that this pain resulted in changes in sleeping habits and in seeking specialized medical care.…”
Section: Discussionsupporting
confidence: 78%
“…Back pain is a common occurrence in young students [1][2][3] , reaching a prevalence of over 60% [4][5][6] , and it is a phenomenon that has been reported in several countries 7 . There are many risk factors that predispose students to back pain, including gender 3,8,9 , age [9][10][11] , intense and competitive physical exercise 3,12,13 , abdominal force and resistance 14 , flexibility 15 , smoking 12,15 , being overweight 5,16, psychosocial factors such as depression and anxiety 17,18 , family history of back pain 13,19 and postural habits [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…b) Others authors [74,104] only gathered measurements that are not defined in the ISO 7250-1. Also, the ISO standard mentioned that it is anticipated that the basic list will be supplemented by specific additional measurements.…”
Section: Procedures For Anthropometric Data Collectionmentioning
confidence: 99%
“…The most common prevalence periods were 1-month (22 studies) [8,, 6-months (7 studies) [34,[42][43][44][45][46][47], followed by 3-months [48][49][50][51] and 1-year prevalence [9,31,34,52] with four studies each. Table 1 summarizes the characteristics of the included studies (author/year, study design, sample characteristics, the pain definition used and measuring tools).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the 3-months period, the NSBP prevalence ranged from 17, 4% [51] to 51, 3% [49]. In the past 6 month the NSBP prevalence ranged from 15, 6% [34] to 61, 1% [44] and in the last year NSBP prevalence ranged from 17, 4% [34] to 54, 1% [31].…”
Section: Narrative Synthesismentioning
confidence: 99%